2003
DOI: 10.1002/ardp.200300795
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Biological Activity, and Docking Studies of New Acetylcholinesterase Inhibitors of the Bispyridinium Type

Abstract: A novel series of acetylcholinesterase (AChE) inhibitors of the bispyridinium type was synthesized and the inhibitory activity against AChE and butyrylcholinesterase (BChE) measured. In essence, the substitution pattern influenced the inhibitory potency against AChE, where the most active bispyridiniumoxime (TMB-4) was bisbenzyl substituted followed by monobenzyl substituted, bismethyl substituted, and unsubstituted derivatives of TMB-4. Hence, the bisbenzyl ether of TMB-4 was further investigated. In order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…Biological Activities Inhibitory activities of the target compounds against AChE and BuChE enzymes were evaluated by modified Ellman's spectrophotometric method. 9,25) Galantamine was used as reference standard. The results were summarized in Table 1 4.38 µM, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Biological Activities Inhibitory activities of the target compounds against AChE and BuChE enzymes were evaluated by modified Ellman's spectrophotometric method. 9,25) Galantamine was used as reference standard. The results were summarized in Table 1 4.38 µM, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7][8][9][10] In addition, quaternary nitrogen cation displays highly positive binding stabilization due to cation-π interactions with amino acid residues in AChE enzyme. [9][10][11][12] Many reports indicated that compounds bearing aromatic/ heteroaromatic rings on lateral parts of pyridinium displayed high AChE inhibitory activity and act as dual binding inhibitors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…of its possibility to inhibit acetylcholinesterase has been published so far. Hence, compound 4 was subjected to a modified Ellman's test 6 in order to check the inhibitory activity towards AChE. 4 inhibited AChE halfmaximally at IC 50 = 319 nM which is about three times higher than for 1-hydroxytacrine (IC 50 = 106 nM) and about 7 times higher than for tacrine (IC 50 = 44 nM), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…There are many research studies dealing with the quantitative structure activity relationship (QSAR) [28][29][30]. QSAR uses structural patterns (position and number of oxime groups, presence and number of quaternary nitrogen) and physico-chemical properties (partition coefficient, pK a ) for predicting the biological activity of a proposed AChE reactivator [31]. However, none of them are able to accurately predict the most active, desired structure.…”
Section: Discussionmentioning
confidence: 99%